EFFECTS OF DIETS WITH DIFFERENT PROTEIN LEVEL FOR COBIA (Rachycentron canadum) GROWTH IN CONTROLLED TANK - Lulus Setianingsih; Limin Santoso; Suryadi Saputra (University of Lampung, 2019)
The feed given to cobia’s juvennile (Rachycentron canadum) still uses expensive factory-made feed to be the basis of this research. This aims of this research to examine the effect of feed formula with different protein levels on optimal growth cobia. This research method used a completely randomized design (CRD) with three treatments and three replications. The treatment in this study were different protein level commercial feed (as control/46%), and formula feed (protein P1 46% and P2 protein 48%). The parameters tested included absolute weight, daily growth rate, feed conversion ratio, protein retention, and survival rate. The data obtained were analyzed by analysis of variance and continued with the duncan test with a 95% confidence interval. The results showed that the growth of absolute weight and daily growth rates generated from each treatment were significantly different (p <0.05), K (80.30 ± 11.20c g and 1.78 ± 0.25c g/day), P1 (21.87 ± 1.95a g and 0.49 ± 0.05a g/day), P2 (37.43 ± 3.29b g and 0.83 ± 0.07b g/day).